Effect of intravenous vitamin C on adult septic patients: a systematic review and meta-analysis - Liang, Huoyan; Mu, Qingqing; Sun, Wenju; Liu, Liming; Qiu, Simin; Xu, Zili; Cui, Yuqing; Yan, Yan; Sun, Tongwen (Frontiers in Nutrition, 2023)
Background: An increasing number of studies indicate that vitamin C (VC) reduces the mortality of adult septic patients, while some articles suggest otherwise. We performed this systematic review and meta-analysis to resolve the discrepancies in reported results concerning the efficacy of VC in septic patients.We comprehensively searched MEDLINE, EMBASE, and the Cochrane Central Register of Controlled trials for randomized controlled trials (RCTs) evaluating the efficacy of intravenous VC (IVVC) on adult septic patients published from inception to November 28, 2022. The quality of outcomes for eligible studies was assessed using the Recommendations Assessment, Development, and Evaluation methodology. The results were analyzed using the pooled mean difference (MD) or risk ratio (RR) and 95% confidence intervals (CIs).Twenty-two studies (3,570 adult septic patients) were included. IVVC treatment did not improve 28-day mortality compared to the control group (RR, 0.92; 95%CI, 0.81-1.04; I 2 = 26%; evidence risk, moderate). IVVC monotherapy decreased mortality (RR, 0.69; 95%CI, 0.52-0.93; I 2 = 57%), whereas combination therapy did not affect mortality (RR, 1.03; 95%CI, 0.90-1.17; I 2 =0%). IVVC has a trend to decrease the mortality of septic patients (RR, 0.83; 95%CI, 0.69-1.00; I 2 = 33%) but did not affect septic shock patients (RR, 1.01; 95%CI, 0.85-1.21; I 2 = 18%). VC reduced the duration of vasopressor use (MD, 95%CI,; evidence risk, very low) but did not influence the incidence of AKI, ICU length of stay, duration of mechanical ventilation.Conclusions: IVVC treatment did not improve the 28-day mortality in septic patients.Subgroup analysis indicated that VC had a trend to decrease the 28-day mortality in patients with sepsis but not septic shock. VC monotherapy, rather than combination therapy, decreases the 28-day mortality in septic patients. The findings imply that Hydrocortisone, Ascorbic acid, Thiamine (HAT) combination therapy is not superior to VC monotherapy for septic patients. These findings warrant further confirmation in future studies, which should also investigate the mechanisms underlying the enhanced efficacy of VC monotherapy in septic patients.